PENDUGAAN CADANGAN KARBON HUTAN JATI (Tectona grandis Linn. F) DENGAN BERBAGAI PERSAMAAN ALOMETRIK PADA BERBAGAI KELAS UMUR JATI - Tommy Triady Ginting; Cahyo Prayogo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The development of forest plantations into one of forestry enterprises is seen as an activity that can reduce emissions by increasing carbon stocks. Measurement of carbon stocks needs to be done to obtain data of carbon stocks stored in a field so that it can be calculated emissions that are released into the atmosphere when there is a fraction of the land cover. In this study, carbon stocks was calculated by estimation method using allometric equations that had been made in previous studies and devoted to the stands of teak (Tectona grandis Linn. F), litter and soil. The study was conducted by dividing the teak plantation with various age classes (KU) of teak plant, ranging from KU 1 to KU 6. KU 1 has age 1 - 10 years, KU 2 has age 11-20 years, KU 3 has age 21 - 30 years old, KU 4 has age 31 - 40 years old, KU 5 has age 41-50 years and KU 6 has age 51 - 60 years old. The value of carbon stocks in the teak stands in each equation increased with the increasing age of the teak stand. Carbon deposits in teak forests increased by 3.96 t ha-1 to 5.54 t ha-1 annually. Teak forests can reduce CO2 in the air, and the greater the age of teak the greater CO2 in the air can be reduced. Teak forests can reduce CO2 in the air by 14.45 t ha-1 to 20.26 t ha-1 annually. Basal area value on teak stands affects 64% of litter biomass values. The higher the basal area value the litter biomass value will increase. Basal area values of teak forests in KU 1 to KU 6 ranged from 5.63 mÂ² ha-1 to 50.36 mÂ² ha-1.